Improved fault analysis tools in unbalanced distribution network: article / Nuramirah Saffee - Saffee, Nuramirah (Universiti Teknologi MARA (UiTM), 2009)
This paper addresses a new approach for a short-circuit analysis algorithm for radial three-phase distribution networks, based on two relationship matrices method, the bus current-injection-to branch-current matrix (BIBC) and branch-current-to bus-voltage matrix (BCBV). Both matrices developed from the topological structures of distribution systems are used to analyze the variations of bus voltages, bus-current injections and branch currents under fault conditions. A short-circuit-analysis method can then be developed from these two matrices and be used to solve the various types of single or simultaneous unsymmetrical faults by using only one model. This model consists of four impedances that their values can be varying from zero to extreme so that each kind of unsymmetrical faults can be simply modeled. Since the proposed method does not use the traditional admittance matrix, the time-consuming procedures such as tri-factorization or inverse of admittance matrix are not necessary. Simulation of IEEE 34-bus and IEEE 4- bus network together with the results obtained such as phase fault currents and voltage profiles are presented and discussed.